2009
DOI: 10.1161/hypertensionaha.108.125211
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Sustained Blood Pressure Lowering by Urocortin 2

Abstract: Abstract-Recently, novel corticotropin-releasing factor-related peptides, named urocortin 1, 2, and 3, and a distinct cardiac and peripheral vascular receptor (corticotropin-releasing factor receptor 2) were described being part of a peripheral corticotropin-releasing factor system modulating cardiovascular function in response to stress. Vasorelaxation and blood pressure lowering have been reported after acute administration of these peptides. No data are available on the acute and chronic effects of urocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Indeed, recent work by Yang et al 19 in spontaneously hypertensive rats (a model also marked by vasoconstriction, as well as an activated renin-angiotensin system) demonstrated that not only does intravenous Ucn1 reduce serum angiotensin-converting enzyme (ACE) and Ang II levels, but a significant positive relationship exists between circulating ACE and systolic blood pressure. In agreement with our study, Dieterle et al 15 have shown sustained blood pressure lowering by Ucn2 in hypertensive salt-sensitive Dahl rats after chronic treatment. This occurred in conjunction with the preservation of left ventricular function (in contrast to the deterioration exhibited in untreated controls) and in the absence of any heart rate increase.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Indeed, recent work by Yang et al 19 in spontaneously hypertensive rats (a model also marked by vasoconstriction, as well as an activated renin-angiotensin system) demonstrated that not only does intravenous Ucn1 reduce serum angiotensin-converting enzyme (ACE) and Ang II levels, but a significant positive relationship exists between circulating ACE and systolic blood pressure. In agreement with our study, Dieterle et al 15 have shown sustained blood pressure lowering by Ucn2 in hypertensive salt-sensitive Dahl rats after chronic treatment. This occurred in conjunction with the preservation of left ventricular function (in contrast to the deterioration exhibited in untreated controls) and in the absence of any heart rate increase.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the observed falls in circulating natriuretic peptide concentrations observed in our study (peptides with a range of beneficial actions in the setting of HF), 24 Ucn2 is reported to stimulate the secretion of ANP and BNP in cardiomyocytes, 25 and ventricular expression of BNP, at least, is reported to be maintained after chronic Ucn2 administration in the rat. 15 Although it is the CRFR1 rather than the CRFR2 subtype responsible for mediating HPA axis activation, 4 the transient rise in plasma cortisol levels seen with chronic infusion of Ucn2 (reportedly selective for CRFR2) was not entirely unexpected given an identical response seen with bolus Ucn2 administration in our previous work. 7 In that earlier study, the concurrent rise in plasma Ucn1 concentrations (and subsequent activation of CRFR1), presumably as a result of competitive inhibition for the CRFR2 by Ucn2, was likely responsible.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Further studies will clarify the role of urocortins in the pathophysiology, diagnosis, and therapeutics of evolving of HF. Ucn-2 may not be as powerful as the natriuretic peptides in the diagnosis of HF for the present, but therapeutic features of Ucn hormone (Ucn-1, Ucn-2 isoforms) (13,(15)(16)(17) are seems to distinctive from the natriuretic peptides.…”
Section: Discussionmentioning
confidence: 88%
“…In a blood sample practically measurement of such determinants may contribute to the improvement of quick diagnosis of HF and could allow to detect the staging of HF. The published results show that Ucn is a diagnostic marker and a potentially attractive therapeutic target for HF (13,(15)(16)(17). Relatively few studies (18)(19)(20) have been performed related to the role of Ucn hormone in humans HF, and there are no sufficiently investigations regarding relation of serum Ucn levels with diastolic dysfunction (DD) or CAD.…”
Section: Introductionmentioning
confidence: 99%